1974
DOI: 10.1073/pnas.71.4.1188
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Newly Synthesized Proteins from Schwann Cells to the Squid Giant Axon

Abstract: The squid giant axon is presented as a model for the study of macromolecular interaction be- teins synthesized in the Schwann cells surrounding the axon are subsequently transferred into the axoplasm. MATERIALS AND METHODSProtein synthesis was studied in squid giant axons obtained from live squid which were kept in a sea tank and used within 48 hr of capture. The giant axons were obtained by decapitating the squid and dissecting the axons under a stream of running sea water. The axons, 4-6 cm long, were tied w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

1975
1975
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 21 publications
4
53
1
Order By: Relevance
“…The results of the experiments with chloramphenicol and puromycin reinforce our previous results and those of others indicating that the incorporation of [3H]leucine into proteins of the squid giant fiber occurs via protein synthesis on eukaryotic ribosomes. In contrast to our previous results on unpaired axons (42), the paired control paradigm indicates that cycloheximide is not a completely effective inhibitor of protein synthesis in the squid giant fiber, since 0.1 mg/ml cycloheximide reduced protein synthesis in the sheath by only 50% when compared with paired controls. Cycloheximide does not completely inhibit protein synthesis in Aplysia ganglia (57), suggesting that this protein synthesis inhibitor may not be effective on intact molluscan neurons.…”
Section: Inhibition Of Amino Acid Incorporation Into Proteins Of the contrasting
confidence: 99%
See 4 more Smart Citations
“…The results of the experiments with chloramphenicol and puromycin reinforce our previous results and those of others indicating that the incorporation of [3H]leucine into proteins of the squid giant fiber occurs via protein synthesis on eukaryotic ribosomes. In contrast to our previous results on unpaired axons (42), the paired control paradigm indicates that cycloheximide is not a completely effective inhibitor of protein synthesis in the squid giant fiber, since 0.1 mg/ml cycloheximide reduced protein synthesis in the sheath by only 50% when compared with paired controls. Cycloheximide does not completely inhibit protein synthesis in Aplysia ganglia (57), suggesting that this protein synthesis inhibitor may not be effective on intact molluscan neurons.…”
Section: Inhibition Of Amino Acid Incorporation Into Proteins Of the contrasting
confidence: 99%
“…These studies confirmed and extended previous observations (20) indicating that squid giant fibers separated from their neuron cell bodies are capable of incorporating labeled amino acids into proteins, some of which appear in the axon (42). The appearance of these labeled proteins in the axon raised an interesting question regarding the site at which these proteins were synthesized.…”
supporting
confidence: 88%
See 3 more Smart Citations